Pengembangan Ekowisata Kawasan Mangrove di Desa Tatakalai, Kecamatan Tinangkung Utara, Kabupaten Banggai Kepulauan - Lisdayati A. Lomba (Fakultas Teknik Universitas Bosowa, 2022)
The purpose of this research is to identify the causes of the unfavorable mangrove area. As well as to find out the development of Ecotourism in the Mangrove Area of Tatakalai Village, Banggai Islands Regency, this research is to determine the cause of the undeveloped mangrove area. And to find out the development of Ecotourism in the Mangrove Area of Tatakalai Village, Banggai Islands Regency.The variables used consist of 5 (five) variables including: (1) Objects and Attractions; (2) Accessibility; (3) Amenity; (4) Public Facilities; (5) Institutional. The analytical method used is descriptive analysis to determine the conditions in the area, then arrange the development of Tatakalai Village as Ecotourism with the SWOT analysis methodSo that in the development of Mangrove Ecotourism in Tatakalai Village as a Tourism Object, namely by socializing the Mangrove Area as the only Tourism Object in North Tinangkung District, increasing tourism contributions to the quality and quantity of human resources, supporting the vision and mission of RIPPARKAB and making it a reference/guideline in tourism development. Increase attractiveness by building and equipping supporting facilities to attract tourists to visit the Mangrove Area in Tatakalai Village and disseminate information on tourist attractions by utilizing information technology